2020
DOI: 10.1101/2020.05.15.090860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multifocal tDCS modulates resting-state functional connectivity in older adults depending on induced electric field and baseline connectivity

Abstract: Background. Advancing age affects the brain's resting-state functional networks. Combining non-invasive brain stimulation (NIBS) with neuroimaging is a promising approach to modulate activity across resting-state functional systems and explore their true contribution to cognitive function in aging. However, substantial individual variability in the response to NIBS has been reported and, hence, identifying the individual predictors of NIBS-induced modulatory effects is crucial if we are to harness their potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…One of the factors limiting the therapeutic potential of tDCS is the high inter-subject variability of behavioural effects. It has been suggested that this might, at least in part, be due to the use of a standard extracranial current intensity across participants, which will inevitably lead to variability in the E-field applied in the cortex [ 21 , 30 , 56 58 ]. Supporting this theory, tDCS-induced behavioural outcomes such as improvements in working memory have been related to the applied E-field [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors limiting the therapeutic potential of tDCS is the high inter-subject variability of behavioural effects. It has been suggested that this might, at least in part, be due to the use of a standard extracranial current intensity across participants, which will inevitably lead to variability in the E-field applied in the cortex [ 21 , 30 , 56 58 ]. Supporting this theory, tDCS-induced behavioural outcomes such as improvements in working memory have been related to the applied E-field [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors limiting the therapeutic potential of tDCS is the high inter-subject variability of behavioural effects. It has been suggested that this might, at least in part, be due to the use of a standard extracranial current intensity across participants, which will inevitably lead to variability in the E-field applied in the cortex (Abellaneda-Pérez et al, 2020; Kim et al, 2014; Laakso et al, 2015; Mezger et al,2021; Soleimani et al, 2021). Supporting this theory, tDCS-induced behavioural outcomes such as improvements in working memory have been related to the applied E-field (Albizu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%